Організація самостійної роботи студентів при вивченні фармацевтичної ботаніки - Корнієвська, Валентина Григорівна; Корниевская, В. Г.; Kornievskаyа, V. G. (ЗДМУ, 2013)
Висвітлено основні принципи впровадження різних форм самостійної роботи студентів у процесі вивчення фармацевтичної ботаніки. Показаны основные принципы внедрения различных форм самостоятельной работы студентов в процессе изучения фармацевтической ботаники. The basis principles of the implementation of different forms of the student’s individual work were discussed in the process of studying parmaceutical botany.
Организация самостоятельной работы студентов при изучении фармацевтической ботаники
Organization of independent work of students in the study of pharmaceutical botany
Keywords: мотиваційні чинники; самостійна робота; форми самостійної роботи; мотивационные факторы самостоятельная работа; формы самостоятельной работы; motivation factors; outclasses work; forms of outclasses work